El enfoque sobre competencias: Una perspectiva crítica para la educación - Jurado Valencia, Fabio (Revista Complutense de Educación, 2009)
Competence is a term with multiple senses. According to its place in a discourse, it’s natural to recognize in every language the meaning of a word. The sense of the term “competence” depends on who is using it and what type of approach it’s been proposed. Language is not neutral, not even the terms. Its use defines its specific sense. In the last two decades the term “competence” has been transformed in a sack-word. Consequently, it exist the ambition to establish a unique sense of the word. In this work I will try to show some of the senses of the term “competence”, and, at the same time, I invite to consider the difference between academic competences and professional competences when we want to orientate the evaluation processes in education.
Keywords: Competence; Knowledge; Information; Language; Unidimensional; Multidimensional; Semiotics; Discourse; Academism; Operationalism; Evaluation; Critical Perspective; Education; Pedagogy; Projects